Natural Sciences teachers' views on Indigenous Knowledge and How to use it in teaching and learning in South African Classrooms - Raphothe, Paseka Nimrod (My University, 2022)
South Africa underwent much curricular change during Apartheid and post-Apartheid. The quality of education provided for black people was the worst during Apartheid; the education they received catered only for menial labour. However, the need to provide quality education to all strata of society took precedence when South Africa became a democratic state in 1994. Moreover, the need to respect different worldviews and knowledge systems from different societies came into focus at this time. Thus, post-Apartheid, revisions to the curriculum led to the current Curriculum and Assessment Policy Statement (CAPS), which mandates that teachers include Indigenous Knowledge (IK) in their teaching and learning of Science. Investigations are required to understand the level of guidance teachers receive on integrating IK into their teaching. The following documents were analysed for this study to examine the guidance provided to teachers CAPS, Annual Teaching Plan (ATP), and the Pacesetter. Three teachers were surveyed to explore their views as well. The focus in this study was grades 8 and 9 Natural Sciences teachers. The study aimed to explore ways in which teachers could integrate IK in their teaching and learning of science to make science more accessible to their learners. The research took a qualitative case study approach and used theoretical frameworks as the lens. Aikenhead and Jegede’s border crossing, Vygotsky's Social constructivism, specifically the More Knowledgeable Other (MKO) and Zone of Proximal Development (ZPD), and Piaget's Cognitive constructivism (a process of accommodation and assimilation). Data was collected using questionnaires and followed up with semi-structured interviews. Thematic content analysis was used to analyse data and develop themes that helped answer the research questions. Findings in this study indicated some misalignment between the different curriculum documents used by teachers with regards to IK. However, the study indicated 3 that teachers are integrating IK into their teaching, as mandated by the CAPS. Some teachers use their experiences learned in the communities they grew up in and integrated that knowledge in their teaching and learner discussion in a Science classroom. This study documents examples used by teachers in their integration of IK into their classroom practice and, therefore, can provide a resource for teacher development in this area. Moreover, documentation of these practical examples of IK integration into classroom practice can be helpful to teachers who seek to facilitate the students’ access to science concepts taught in Natural Sciences.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Natural Sciences Teachers; Indigenous Knowledge; Teaching and Learning